An exploratory study on design process in architecture: perspective of creativity - Dash, Shanta Pragyan (Creativity Studies, 2021)
Any design challenge could be solved by identifying systemic complexity in the issue before following any problem-solving process. Designers approach problems in different forms but historically worked effectively to build a template or phase sequence. The design process can be used by designers virtually in any project which plays a crucial role in designing innovative architectural projects for many architects. Many studies were conducted to analyze, review, compare and recommend several creative approaches to problem management that allow designers to recognize their work and propose new solutions. However, there are not many studies on the stages to follow to undergo a comprehensive design process in architecture. This study aims to review the various stages involved in the design process. Firstly, it addresses the conceptualization phase of design critically examining the creativity and ideation process with creative and strategic thinking. Secondly, it discusses the representation of the design process expressing through storyboards and animatic, computer-aided design and building information modeling, and virtual reality and augmented environments. Thirdly, it discusses design assessment stage where the techniques for assessment of creativity in design and simulation for analyzing users’ perspective is explained. In the conclusions of the paper, a discussion has been made on an inter-relationship between the various stages in the design process and its relevance for a comprehensive understanding of the architectural integrative design process to address any design challenge both as a studio project for architecture students or in live projects by the practicing architects.